Gastrointestinal stromal tumor (GIST) with liver metastases: An 18-year experience from the GIST cooperation group in North China. Issue 46 (November 2017) - Shi, Yi-Nan; Li, Yong; Wang, Li-Ping; Wang, Zhen-Hua; Liang, Xiao-Bo; Liang, Han; Zhang, Li; Li, Bin; Fan, Li-Qiao; Zhao, Qun; Ma, Zhi-Xue; Zhao, Xue-Feng; et al.
Abstract : Abstract: Approximately 40% to 50% of gastrointestinal stromal tumor (GIST) patients will have recurrence or metastases after resection of the primary lesion, and the most common affected sites will be liver and peritoneum. Imatinib has been considered as the first-line therapy of metastatic GIST. Surgery for metastases is proposed when possible. Furthermore, there are controversies concerning hepatic resection and systemic tyrosin kinase inhibitors (TKIs). The therapeutic conditions and long-term outcome of GIST patients with liver metastases in northern China remain unknown. The clinical, pathological, and follow-up data of 144 GIST patients, who had liver metastases between June 1996 and June 2014 from 3 tertiary cancer centers in northern China, were reviewed. Thirty-two cases (22.2%) had hepatectomy with 23 (23/32, 71.9%) R0 resections and 9 (9/32, 28.1%) R1/R2 resections, respectively. Twenty-three patients were given imatinib postoperatively. Furthermore, 98 (68.1%) patients were given TKIs only to control disease progression, and sunitinib was considered after imatinib failure in 12 patients. The 1-, 3- and 5-year survival rate was 82%, 51%, and 24%, with a median overall survival of 48 months for all patients. Patients who had hepatic resection combined with TKIs had a tendency of improved outcome, and the median survival time was 89 months. This was in contrast to patients who received TKIs only, in which median survival time was 53 months. Patients who received imatinib plus sunitinib had a tendency of longer survival time, compared with patients who received imatinib only (not reached vs 50 months). TKIs combined with hepatic resection had a role in improving the outcome of GIST patients with liver metastases.